2013
DOI: 10.1021/es304385y
|View full text |Cite
|
Sign up to set email alerts
|

Methylmercury is the Predominant Form of Mercury in Bird Eggs: A Synthesis

Abstract: Bird eggs are commonly used in mercury monitoring programs to assess methylmercury contamination and toxicity to birds. However, only 6% of >200 studies investigating mercury in bird eggs have actually measured methylmercury concentrations in eggs. Instead, studies typically measure total mercury in eggs (both organic and inorganic forms of mercury), with the explicit assumption that total mercury concentrations in eggs are a reliable proxy for methylmercury concentrations in eggs. This assumption is rarely te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
76
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 83 publications
(78 citation statements)
references
References 34 publications
(60 reference statements)
2
76
0
Order By: Relevance
“…Fourth, data for both total mercury and methylmercury were included. All mercury in eggs (Ackerman et al, 2013), whole blood (Rimmer et al, 2005), muscle (Scheuhammer et al, 1998), and feathers (Thompson and Furness, 1989) was assumed to be in the methylmercury form, and, therefore, total mercury and methylmercury concentrations were used to represent methylmercury concentrations in birds. A significant proportion of the mercury in liver and kidney can be in the inorganic form (Eagles-Smith et al, 2009b; Scheuhammer et al, 1998; Thompson and Furness, 1989).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Fourth, data for both total mercury and methylmercury were included. All mercury in eggs (Ackerman et al, 2013), whole blood (Rimmer et al, 2005), muscle (Scheuhammer et al, 1998), and feathers (Thompson and Furness, 1989) was assumed to be in the methylmercury form, and, therefore, total mercury and methylmercury concentrations were used to represent methylmercury concentrations in birds. A significant proportion of the mercury in liver and kidney can be in the inorganic form (Eagles-Smith et al, 2009b; Scheuhammer et al, 1998; Thompson and Furness, 1989).…”
Section: Methodsmentioning
confidence: 99%
“…When moisture content was not reported, an average moisture content of 79% in blood, 67% in liver, 70% in muscle, and 74% in kidney was used (Eagles-Smith et al, 2008). For eggs, it is important to report mercury concentrations on a fresh wet weight (fww) basis (Ackerman et al, 2013; Stickel et al, 1973); however, the necessary egg morphometrics to make these adjustments were not available in many of the raw datasets and this made the conversion to fresh wet weight not possible. Therefore, when egg morphometric data were unavailable, egg THg concentrations (μg/g) were converted on a dry weight basis into a wet weight basis using the reported percent moisture in the individual egg or, when moisture content was not reported, an average egg moisture content of 75% was used (Ackerman et al, 2013).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Different forms of mercury (species) occur in the environment, with methylmercury (MeHg) readily accumulating in organisms due to its affinity for cellular proteins (Dietz et al, 2013), and thereby accounting for the majority of the mercury found within tissues in higher trophic levels of a system (>90%; Ackerman et al, 2013), compared to inorganic mercury species. MeHg may be detrimental to organisms because it has negative impacts on their physiology, including acting as a neurotoxin and immunotoxin (Wolfe et al, 1998).…”
mentioning
confidence: 99%
“…The relatively high mercury concentrations in CLTE could also reflect conditions at their overwintering area, as has been shown in some migratory populations of CATE and DCCO in the central US and Canada (Lavoie et al, 2015). Because mercury is not lipophilic like POPs (Ackerman et al, 2013), seabirds may have limited capacity to excrete body-bound mercury via burning adipose tissue, a decretion pathway that has been suggested for POPs.…”
Section: Seabird Toxicant Exposure: Differences Among Speciesmentioning
confidence: 85%